Event and relationship marketing strategies in the post-COVID Bali tourism industry: Exploring the mediating effect of satisfaction on loyalty - Mahendri, Ni Made Kiki; Astuti, Widhy Tri (Goodwood Publishing, 2025)
Purpose: This study investigates how event marketing and relationship marketing influence customer loyalty in Bali’s tourism industry during the post-COVID recovery period. Satisfaction is tested as a mediating variable to explore the mechanism through which these marketing strategies impact loyalty. Methods: A quantitative research design was used with a survey distributed to 200 tourists who participated in tourism-related events in Bali. Structural Equation Modeling (SEM) was employed to analyze the direct and indirect effects between variables, using satisfaction as a mediator. Results: The results indicate that both event marketing and relationship marketing significantly and positively affect customer satisfaction and loyalty. Satisfaction was found to partially mediate the relationship between marketing strategies and loyalty, confirming its strategic role in post-crisis recovery efforts. Conclusion: Strategic marketing through events and long-term relationships contributes to the enhancement of tourist loyalty, with satisfaction acting as a critical driver. The findings highlight the importance of personalized and memorable experiences in rebuilding tourism post-pandemic. Limitations: The study is limited to event-based tourists in Bali and may not be generalizable to other sectors or regions. Contribution: This study contributes empirical evidence on the integrated effects of event marketing and relationship marketing on loyalty in a post-crisis tourism context. By confirming satisfaction as a partial mediator, the research strengthens theoretical understanding of experiential and relational strategies in hospitality marketing and offers practical insights for tourism businesses seeking to improve loyalty through customer-centered experiences.